Spiritual Leadership Enhances Caring Behaviour: The Mediating Role of Calling - Candrawati, Sang Ayu Ketut; Sriani, Ni Kadek Ayu; Subhaktiyasa, Putu Gede; Andini, Ni Komang Sukra; Putri, Ni Luh Nova Dilisca Dwi; Citrawati, Ni Ketut; Andriany, Megah (Nurse Media Journal of Nursing, 2024)
Background: Caring behaviour is essential for patient health; however, it is often not practised optimally. Therefore, spiritually-based leadership is required to encourage this behaviour. Unfortunately, research investigating the ability of spiritual leadership to enhance caring behaviour through spiritual well-being is limited.Purpose: This study aimed to examine the impact of spiritual leadership and spiritual well-being in the form of calling and membership on caring behaviour.Methods: This study employed an explanatory quantitative design with a cross-sectional approach. One hundred fourteen inpatient nurses who provided comprehensive patient care were selected using a total sampling technique. Data were collected using the Spiritual Leadership Questionnaire and the Caring Behaviours Inventory. The analysis adopted partial least squares structural equation modelling (PLS-SEM) using a second-order reflective-formative model.Results: The findings demonstrate that spiritual leadership has a significant direct effect on caring behaviour (t=3.976, p=0.000), calling (t=4.672, p=0.000), and membership (t=2.845, p=0.005). However, the direct impact of membership on caring behaviour was insignificant (t=1.298, p=0.194). Calling proved to mediate the effects of spiritual leadership on caring behaviour (t=3.145, p=0.002), while membership could not function as a mediator (t=1.197, p=0.231).Conclusion: This study emphasizes the importance of spiritual leadership in nursing care, particularly in enhancing nurses’ caring behaviours. Healthcare organizations should implement training programs on spiritual leadership to encourage calling nurses to perform their duties with dedication. Developing nurse membership should be considered, but the main focus must be on strategies that strengthen nurses’ calling, as this is an essential factor in providing quality and empathetic care.